Targeting Growth Factor and Cytokine Pathways to Treat Idiopathic Pulmonary Fibrosis - Ma, Hongbo; Liu, Shengming; Li, Shanrui; Xia, Yong (Frontiers in Pharmacology, 2022)
Idiopathic pulmonary fibrosis (IPF) is a chronic interstitial lung disease of unknown origin that usually results in death from secondary respiratory failure within 2-5 years of diagnosis. Recent studies have identified key roles of cytokine and growth factor pathways in the pathogenesis of IPF. Although there have been numerous clinical trials of drugs investigating their efficacy in the treatment of IPF, only Pirfenidone and Nintedanib have been approved by the FDA. However, they have some major limitations, such as insufficient efficacy, undesired side effects and poor pharmacokinetic properties. To give more insights into the discovery of potential targets for the treatment of IPF, this review provides an overview of cytokines, growth factors and their signaling pathways in IPF, which have important implications for fully exploiting the therapeutic potential of targeting cytokine and growth factor pathways. Advances in the field of cytokine and growth factor pathways will help slow disease progression, prolong life, and improve the quality of life for IPF patients in the future.